2017 Jakarta Election and Indonesia’s Democracy, Jakarta’s Contentious Election: What Anies Baswedan’s Victory Means - Syailendra, Emirza Adi (2017)
Jakarta’s 2017 Gubernatorial Election is Indonesia’s most discussed political event so far. Marked by tacit competition between oligarchs and the mobilisation of religion-related issues to capture votes, the victory of Anies Baswedan to unseat Ahok as governor has raised questions about the prospects in the 2019 presidential election.